Pendidikan Keaksaraan di Lapas Kelas III Rangkasbitung: Upaya Meningkatkan Literasi bagi Warga Binaan - Pratiwi, Destia; Fauzi, Ahmad (Lembaga Yasin AlSys, 2025)
This study is motivated by the persistently low literacy levels in correctional institutions, including at Lapas Kelas III Rangkasbitung, which poses a serious challenge to the social rehabilitation process of inmates. Many lack basic reading and writing skills, limiting their access to information and education. The aim of this research is to examine the implementation of literacy education programs as an effort to improve literacy among inmates. A qualitative approach was used, with data collected through observation, in-depth interviews, and documentation of programs conducted by university students. The findings show that the literacy program was implemented in stages, starting with the introduction of alphabet letters, construction of syllables, and progressing to reading simple sentences using relevant reading materials. The learning process was adapted to individual abilities, employing a personalized approach with direct mentoring. The program demonstrated significant progress, evidenced by improved literacy skills among inmates, increased self-confidence, and enthusiasm for learning. These findings affirm that literacy education in correctional institutions plays a strategic role in fulfilling the fundamental right to education and serves as a means of rehabilitation and empowerment, fostering positive thinking and opening opportunities for social reintegration after incarceration.